World's Fair Grand March - D.W. Crist::::::::: (D.W. Crist)
At head of title: Respectfully dedicated to Dr. and Mrs. A.J. Hill, North Lawrence, Ohio On cover: For the piano or cabinet organ Also on cover is portrait of Crist Publishers advertisements on verso of last leaf.